(untitled) (Archives of Criminology, 2023)
Human trafficking is an umbrella term that covers sexual, labour and other forms of exploitation. The process of exploitation for different purposes involves the user, the victim and the exploiters. In this study, we focus on the actors outside this process, who are nevertheless important in tackling the phenomenon: the police officers, prosecutors and judges who deal with trafficking cases. Hungarian law enforcement officers are not used to investigating their attitudes and formulating their own opinions about particular phenomena. However, being able to provide them with even more effective and appropriate training would be extremely important for the organisation and for the phenomenon itself. We asked permission from leaders of various members of the criminal justice system (police, prosecutor office, judge) to conduct an attitude test among their staff. In this article we present the situation in Hungary of combating human trafficking and we summarise the survey results.